Revolutionizing Playing with Skeleton Atoms: Molecular Editing Surgery in Medicinal Chemistry - Rabie, Amgad M. (Mini Reviews in Medicinal Chemistry, 2025)
Finding the most perfect drug candidates in the fields of drug discovery and medicinal chemistry will remain the main interest of drug designers. This concern necessitates organic and medicinal chemists, in most examples, to precisely design and search for drug candidates that are very analogous to the present effective drugs with solving, mainly, their proven critical pharmacological and clinical issues through slightly changing one or two atoms of the principal functional skeletons of the molecules of these present therapeutics by atom swapping, removal, and/or addition procedures in organic chemical synthesis. This accurate modern chemicosimilarity tactic in drug discovery surely saves time while keeping us very close, or sometimes highly superior, to the parent pharmacophoric bioactivity (i.e., keeping considerable analogy to the parent therapeutic molecule). From this perspective and logic, the science of skeletal editing of molecules (i.e., skeletal molecular editing) arose in the era of artificial intelligence (AI) and its dramatic predictions. As a pioneer in this modern branch in pharmaceutical and therapeutic organic chemistry, in this up-to-date minireview and perspective article, an attempt was made to introduce skeletal editing and its synthetic surgeries (over molecules) to the audience (including irrelevant readers) in a simpler and more attractive way as a novel chemical technology, highlighting the previous synthetic trials (in general), demonstrating the three main techniques, and, finally, discussing the future therapeutic needs and scenarios from a medicinal chemist's viewpoint.
Keywords: drug discovery